Measuring the Diffusion Characteristic of Block Ciphers: The Bit Relationship Test (BRT) - Bhowmik, Dipanjan; Datta, Avijit; Sinha, Sharad (International Journal of Computer Sciences and Engineering, 2015)
The paper describes a test aimed at measuring the diffusion characteristic of block ciphers. Cryptographic strength of a cipher is directly proportional to the extent to which diffusion is achieved by the underlying cipher, which is measured using the test described in the paper. The paper also enlists the results obtained from the test on various block ciphers. The test algorithm described in the paper will be subsequently added as part of the already existing varied test suite to act as a distinguisher based on the diffusion characteristic of the underlying cipher.